Comparison of Multiple-Choice Questions in Quality Parameters of Pediatric Residency Tests between the Pre-Board Examination of Tabriz University of Medical Sciences and National Board Examination in 2007 and 2011 - Mohammad Barzegar; Nemat Bilan; Mohammad Hassan Karegar Maher; Siamak Shiva; Manizheh Sayyah Melli; Aydin Tabrizi (Tabriz University of Medical Sciences, 2014)
Introduction: The objective of this study was to compare Multiple-Choice Questions (MCQs) quality parameters of pediatric residency tests between the pre-board examinations of Tabriz University of Medical Science (TUMS), Tabriz, Iran and the national board examination in 2007 and 2011. Methods: In this cross-sectional study, we evaluated the format of 300 MCQs in the pre-board examination of TUMS and the format of 300 MCQs of the national board examination in pediatric residency. Individual MCQs were evaluated for content budgeting according to the Nelson pediatric residency reference textbook, taxonomy levels (Bloom's levels I, II and III) and following structural principles (based on Millman checklist). Data were analyzed by SPSS (version 18) software. Results: We find more consistent content budgeting in the national board MCQ examinations. Forty one percent of pre-board MCQ examinations and 72% of national board MCQ examinations were Bloom's taxonomy levels II -III (P=0.000). We found correct structural principles in 69.2% and 76.2% of pre-board and national board MCQs examinations, respectively (P=0.05). 30.7% and 22.5% of pre-board and national board MCQs examinations were negative stem, respectively (P=0.025). Most of the negative stem MCQs were Bloom's taxonomy level I questions. Conclusion: Pediatric residency pre-board MCQ examinations of TUMS were of a significantly lower level of learning (taxonomy level I) compared to the national board MCQ examinations. To prevent low quality development of internal university examinations, monitoring of these exams is recommended.